Development of a horizontal transmission model to assess the effects of exposure to pathogenic E. cecorum during the hatching phase in broiler chickens - James Higuita; Marcela Arango; Aaron Forga; Mitch Rowland; Jundi Liu; Ross Wolfenden; Danielle Graham (Poultry Science)
Due to the emergence of virulent Enterococcus cecorum (EC) in young broiler chicken flocks, the transmissibility of EC during late embryogenesis needs to be defined. The purpose of the present study was to develop a horizontal transmission model to simulate exposure to virulent EC during the hatching phase. In Exp 1, EC5, EC7, or EC11B (∼104 CFU/embryo) was administered to a subset of the embryos, deemed seeders, by in ovo injection into the amniotic cavity at day 19 of embryogenesis. Seeders were comingled with non-infected embryos, or contacts, for the remainder of embryogenesis. The experiment consisted of 7 treatment groups: (1) non-challenged control (NC), (2) EC5 Contacts, (3) EC5 Seeders, (4) EC7 Contacts, (5) EC7 Seeders, (6) EC11B Contacts, and (7) EC11B Seeders. Increased EC recovery from gut and liver/spleen at hatch for Groups 2-7 indicated that horizontal transmission occurred. Exp 2 was conducted to assess the effect of direct or indirect exposure to EC during late embryogenesis on disease progression and 26-day performance. CHROMagar™ Orientation agar was used to determine EC recovery followed by MALDI-TOF. The ANOVA was used to determine significant differences (P<0.05) for average body weight (BW) and average body weight gain (BWG) and EC quantification (Log10 CFU) with means being further separated using Student's t test. Chi-square was used to evaluate significant differences for hatchability, mortality, macroscopic lesions, and EC incidence. BWG was significantly (P<0.05) lower for Groups 2-5 compared to NC. Splenic EC recovery was increased in Groups 2-5, with detection being highest in Groups 3 and 5. More notably, EC recovery from the FTV was significantly higher across Groups 2-7 compared to NC at d26. Gross lesions were observed for the heart, liver, and spleen across Groups 2-7. These results suggest that horizontal transmission of EC in commercial hatch cabinets could be possible, and that persistent EC colonization and organ involvement may affect performance and disease progression in young broiler chickens depending on the EC strain. Novel strategies to control EC infections pre- and post-hatch could be evaluated using the model developed herein.